2001
DOI: 10.1021/bi010065u
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinctive Cell Binding Patterns by Vacuolating Toxin Fused with GlutathioneS-Transferase:  One High-Affinity m1-Specific Binding and the Other Lower-Affinity Binding for Variant m Forms

Abstract: The Helicobacter pylori VacA causes large intracellular vacuoles in epithelial cells such as HeLa or RK13 cells. Two major VacA forms, m1 and m2, divergent in an approximately 300 amino acid segment within the cell binding domain P58, display distinct cell-type specificity. Sequence analysis of four vacA alleles showed that a m1-like allele (61) and two m2 alleles (62 and v226) mainly differed in the midregion and that v225, a m1m2 chimera, was a natural double crossover from v226 and another allele. Each of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 43 publications
2
39
0
3
Order By: Relevance
“…7). In support of this model, several previous studies have provided evidence indicating that amino acid sequences in the p55 domain of p88 VacA contribute to the process of VacA binding to cells (39,(45)(46)(47). In the current study, binding of p33 to the cell surface, followed by the addition of p55 (p33 1 , p55 2 ), did not result in detectable cell vacuolation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…7). In support of this model, several previous studies have provided evidence indicating that amino acid sequences in the p55 domain of p88 VacA contribute to the process of VacA binding to cells (39,(45)(46)(47). In the current study, binding of p33 to the cell surface, followed by the addition of p55 (p33 1 , p55 2 ), did not result in detectable cell vacuolation.…”
Section: Discussionsupporting
confidence: 86%
“…It has been suggested that the p33 and p55 fragments represent two domains or subunits of VacA (6,28,31,42). Several lines of evidence indicate that amino acid sequences located within a hydrophobic region near the amino terminus of the p33 domain are required for the formation of anion-selective membrane channels (13,23,43,44), and that the p55 domain is responsible for VacA binding to mammalian cells (39,(45)(46)(47). However, detailed analysis of the functional roles of p33 and p55 domains has not been performed.…”
mentioning
confidence: 99%
“…1A) (3). We identified and excluded two m1/m2 chimeric VacA proteins (from strains ch2 and v225) in which tracts of recombination between m1 and m2 sequences were identifiable by eye (4,14,54). VacA sequences were classified as s1 or s2 based on the absence or presence, respectively, of a 9-amino-acid insertion in the signal sequence region (3).…”
Section: Methodsmentioning
confidence: 99%
“…Within this Ϸ281-aa midregion (roughly corresponding to amino acids D455 to V735 in the VacA sequence of H. pylori strain 60190), the amino acid sequences of types m1 and m2 VacA proteins are only Ϸ55% identical. Differences in cell-type specificity have been noted for types m1 and m2 VacA proteins, a phenomenon that may result from binding of m1 and m2 VacA proteins to different cell-surface receptors (36)(37)(38)(39). With the rare exception of a few m1/m2 chimeras, there has been little evidence of recombination between m1 and m2 vacA alleles within the vacA midregion, and, therefore, a phylogenetic distinction between m1 and m2 VacA sequences has remained intact (35).…”
mentioning
confidence: 99%